Sintesa dan Karakteristik Selulosa Asetat Berbahan Kapuk dengan Solution Process - Saputra, Andika Wahyu; Wibyantri, Gabriella Ananda; Suprihatin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Cellulose acetate is a derivative of cellulose that has high commercial value and is widely used in various industries such as textiles, plastics, and paints. This study aims to synthesize and analyze the characteristics of cellulose acetate derived from kapok fiber (Ceiba pentandra) using the solution process method. The synthesis process includes delignification, bleaching, activation, acetylation, and hydrolysis stages. The variables tested in this research were the volume of glacial acetic acid (8–40 mL) and the acetylation time (60–150 minutes). The analysis results showed that the highest acetyl content of 39.92% was obtained at an acetylation time of 90 minutes and an acetic acid volume of 40 mL, with a degree of substitution reaching 2.466, classified as cellulose diacetate according to the Indonesian National Standard (SNI). FTIR spectra confirmed the presence of characteristic functional groups of cellulose acetate, such as the carbonyl (C=O) and ester (C–O) groups from the acetyl group. This study demonstrates that kapok fiber is a potential raw material for producing high-quality cellulose acetate.